2006
DOI: 10.1152/ajpcell.00303.2005
|View full text |Cite
|
Sign up to set email alerts
|

Tastants evoke cAMP signal in taste buds that is independent of calcium signaling

Abstract: We previously showed that rat taste buds express several adenylyl cyclases (ACs) of which only AC8 is known to be stimulated by Ca 2ϩ . Here we demonstrate by direct measurements of cAMP levels that AC activity in taste buds is stimulated by treatments that elevate intracellular Ca 2ϩ . Specifically, 5 M thapsigargin or 3 M A-23187 (calcium ionophore), both of which increase intracellular Ca 2ϩ concentration ([Ca 2ϩ ]i), lead to a significant elevation of cAMP levels. This calcium stimulation of AC activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 46 publications
4
40
1
Order By: Relevance
“…Decades ago, Striem et al [101] reported that treating membranes derived from the anterior surface of rat tongues with sucrose stimulated adenylyl cyclase, implying the presence of G as proteins and Focussed search with primers based on synaptic glutamate receptors cAMP pathways in taste. These studies have been replicated and extended, using intact taste tissue [102]. Further, cAMP depolarizes frog and mouse taste cells, presumably due to cAMP-dependent protein kinase-phosphorylating and closing potassium channels [103,104].…”
Section: Second-messenger Cascades and Taste Gpcrsmentioning
confidence: 83%
See 1 more Smart Citation
“…Decades ago, Striem et al [101] reported that treating membranes derived from the anterior surface of rat tongues with sucrose stimulated adenylyl cyclase, implying the presence of G as proteins and Focussed search with primers based on synaptic glutamate receptors cAMP pathways in taste. These studies have been replicated and extended, using intact taste tissue [102]. Further, cAMP depolarizes frog and mouse taste cells, presumably due to cAMP-dependent protein kinase-phosphorylating and closing potassium channels [103,104].…”
Section: Second-messenger Cascades and Taste Gpcrsmentioning
confidence: 83%
“…Indeed, direct measurements of cAMP after bitter taste verified that this second messenger declines with bitter stimulation [107]. Trubey et al [102] also showed that umami-taste stimulation also causes a decrease in cAMP in rat taste buds, emphasizing the presence of transducin-like G proteins in taste cells. That G a gustducin is intimately involved in bitter, umami, and sweet stimulation has been verified by showing that these taste qualities are significantly compromised in G a gustducin knockout mice [108][109][110][111].…”
Section: Second-messenger Cascades and Taste Gpcrsmentioning
confidence: 97%
“…That leaves the question of how caffeine can stimulate GAS via TAS2Rs. So far, only for sweet and glutamate taste receptors (TAS1R1/3) has an increase of cAMP levels via activation of adenylyl cyclase been demonstrated (39). The signaling cascade of bitter taste receptors has been proposed to reduce cAMP levels by activation of PDE via α-gustducin or transducin (23,26,40).…”
Section: Discussionmentioning
confidence: 99%
“…With such a diversity of CASR-mediated intracellular signaling, it is not unlikely that instead of Ca 2+ mobilization in type I cells, CASR is coupled to some other signaling pathways, perhaps, with cAMP as a second messenger (see Hofer and Brown, 2003;Hofer et al, 2004;Breitwieser et al, 2004). Consistent, at least in the case with Glu, is that this amino acid has been documented to modulate cAMP production in the taste tissue (Abaffy et al, 2003;Trubey et al, 2006), although a cellular source of Glu-dependent cAMP signals and the underlying mechanisms remain to be identified.…”
Section: Discussionmentioning
confidence: 99%